Photoabsorption markers of pressure-induced phase changes in small mercury clusters. A case study on Hg8 - Šarmanová, Martina; Vítek, Aleš; Ćosić, Rajko; Kalus, René (RSC advances, 2019)
Photoabsorption spectra of Hg8 have been calculated at various cluster temperatures and external pressures. A diatomics-in-molecules method has been used to model cluster electronic structure and classical isothermal-isobaric Monte Carlo simulations have been employed for sampling representative cluster configurations. Contributions of different structural isomers of the Hg8 cluster have been analyzed and related to structural transitions in the cluster, particularly those induced by an increased pressure.